Héctor Correa (comp.), Analytical Models in Educational Planning and Administration, Amsterdam, North Holland, 1975 - Serra Puche, Jaime (El Colegio de México A.C., 1979)
Héctor Correa (Comp.), Analytical Models in Educational Planning and Administration, Amsterdam, North Holland, 1975.